Spectrum of common Hodgkin lymphoma and non-Hodgkin lymphomas subtypes in Zambia: a 3-year records review - Pascal Polepole; Victor C. Mudenda; Sody M. Munsaka; Luwen Zhang (BMC, 2021)
Abstract Background Lymphomas usually present with different occurrence patterns across different geographical locations, but their epidemiology in Zambia is yet to be extensively explored. Objectives To study the spectrum of lymphoma subtypes prevalent within the Zambian population. Methods Histopathological records with suspected lymphoma at the University Teaching Hospital (UTH) in Lusaka from the year 2014 to 2016, diagnosed based on the 2008 World Health Organization (WHO) criteria were reviewed. The analysis was done in terms of type, sex, age, and site of biopsy; and Fisher's exact test was used for significance testing. Results During the study period (2014-2016), there were more B cell neoplasms {222 (92.5%)} than T cell neoplasms {18 (7.5%)}. Non-Hodgkin's lymphoma (NHL) was seen in 191 (79.6%) whereas classic Hodgkin's lymphoma (CHL) was seen in 39 (16.3%). Burkitt's lymphoma (BL) and diffuse large B cell lymphoma (DLBCL) showed equal proportions {17.5% of all lymphoma cases (42/240) each}, as the most prevalent subtypes of NHL whereas marginal zone B cell lymphoma was the rarest subtype with 1.4% (4/240). For CHL, mixed cellularity and lymphocyte rich subtypes (4.6% of all lymphoma cases) were the most common subtypes. There was a statistically significant difference in the occurrences of lymphoma subtypes across different age categories (p = 0.002). Conclusion Zambia has a diverse lymphoma subtypes population, affecting a relatively young population. The data from this study will serve as a baseline for improved health care provision and more robust future studies.